2014
DOI: 10.1371/journal.ppat.1003936
|View full text |Cite
|
Sign up to set email alerts
|

A Polysaccharide Virulence Factor from Aspergillus fumigatus Elicits Anti-inflammatory Effects through Induction of Interleukin-1 Receptor Antagonist

Abstract: The galactosaminogalactan (GAG) is a cell wall component of Aspergillus fumigatus that has potent anti-inflammatory effects in mice. However, the mechanisms responsible for the anti-inflammatory property of GAG remain to be elucidated. In the present study we used in vitro PBMC stimulation assays to demonstrate, that GAG inhibits proinflammatory T-helper (Th)1 and Th17 cytokine production in human PBMCs by inducing Interleukin-1 receptor antagonist (IL-1Ra), a potent anti-inflammatory cytokine that blocks IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 34 publications
3
121
0
Order By: Relevance
“…For instance, Cryptococcus elaborates a dense polysaccharide capsule, which shields cell wall carbohydrates from detection by the immune system (15,16). As cell wall carbohydrates are the primary PAMPs in fungal pathogens, we focused our analysis on carbohydrates that are known or suspected to provoke an immune response in other fungal species, including mannan (17)(18)(19)(20), ␤-1,3-glucan (21-30), galactosaminogalactan (GAG) (31)(32)(33)(34)(35)(36), and chitin (37)(38)(39)(40)(41)(42)(43)(44)(45). Freshly harvested Exserohilum rostratum spores were grown in complete RPMI at 37°C with 5% CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Cryptococcus elaborates a dense polysaccharide capsule, which shields cell wall carbohydrates from detection by the immune system (15,16). As cell wall carbohydrates are the primary PAMPs in fungal pathogens, we focused our analysis on carbohydrates that are known or suspected to provoke an immune response in other fungal species, including mannan (17)(18)(19)(20), ␤-1,3-glucan (21-30), galactosaminogalactan (GAG) (31)(32)(33)(34)(35)(36), and chitin (37)(38)(39)(40)(41)(42)(43)(44)(45). Freshly harvested Exserohilum rostratum spores were grown in complete RPMI at 37°C with 5% CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In these conditions, with whole-blood PMN activation by GG, a polysaccharide extracted from A. fumigatus, we demonstrated that NK cells are a critical trigger of PMN apoptosis. In addition, the proapoptotic effect of GG on PMNs was observed at a concentration of 20 mg/ml, which is a relevant concentration in vivo, because Aspergillus can secrete GG in a concentration of 50 mg/ml (44).…”
Section: Discussionmentioning
confidence: 99%
“…GAG is an important anti-inflammatory polysaccharide of the cell wall of A. fumigatus that induces the anti-inflammatory cytokine IL-1Ra [46]. The absence of GAG in the cell wall of A. nidulans [47] may contribute to its proinflammatory capacity, yet this does not explain the additional high induction of an IL1Ra response.…”
Section: Discussionmentioning
confidence: 99%